The Value of Networks Against Food Waste: The Case of “Too Good To Go” - Fragapane, Stefania; Mortara, Ariela (Italian Sociological Review, 2022)
The article addresses the issue of food waste through the study of the Too Good To Go (TGTG) movement and the contribution that the app has made to raising user awareness in the fight against food waste. After highlighting the phenomenon at European and national level, the article focuses on the awareness and motivation of the users of the TGTG app through the analysis of the discussions in two Facebook groups, among the most numerous in Italy, supported by some data from a qualitative survey conducted on a sample of Italian consumers. The analysis highlights a large presence of the TGTG initiative on the national territory in different Italian regions. The growing number of users of the app shows that the initiative is also successful in Italy. However, users seem to place more emphasis on saving money and the quality of food than on the joint project to combat food waste.